Alignment of the Portfolio of IT Projects with the IT Governance in Spanish Universities - Valverde Alulema, Francisco Xavier; Llorens, Faraón (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
This research considers a rubric to assess the portfolio implemented in universities and its alignment with the IT governance principles established by ISO/IEC 38500. The rubric considers 16 elements. It estimates the relationship with 21 possible advantages of implementing the portfolio with some of the elements present. And it compares and establishes the level of coincidence with the real benefits perceived by the universities. This rubric has been applied to the public universities of the Spanish university system. It is concluded that a high percentage of the portfolios implemented have a clear strategic focus and are aligned with IT governance.